Vicente, el elefantito - Moser, Erwin (Barcelona : Grupo Editorial Norma, 1998)
Lost from his herd, Vicente, a very small elephant, wanders through a series of adventures and finds an unusual home.
K-3
Text in Spanish.
Translation of: Vicente der Elefant.
K-3
Keywords: Elephants -- Fiction; Animals -- Fiction; Spanish language materials; Elephants -- Fiction; Animals -- Fiction; Spanish language